Penned in eaudiobook - Cahoon, Lynn (Farm-to-Fork Mystery, 2020)
Angie Turner, chef at Idaho's finest farm-to-table restaurant, has organized a team-building event at a haunted prison, only to find a real-life murderer in their midst . . . Contented employees make for a successful restaurant, which is why the County Seat's crew goes on a quarterly out-of-office meeting. This time, the location is the Old Idaho Penitentiary near the Boise Foothills, a prison brimming with ghostly lore. The lock-in features actors role-playing as guards, fascinating prison stories . . . and an unscripted murder. Who sentenced one of the faux guards to a very authentic death? Angie, her boyfriend, and the County Seat gang are locked in with a killer—excellent motivation for a little sleuthing. Between ghostly apparitions and flesh-and-blood suspects, Angie's plate is full, but will her luck, and her life, hold out until the gates reopen at dawn?